An analysis of the competitiveness of the furniture industry in the Valencian Community - Juan Ignacio Dalmau; Blanca De Miguel; Maria del Val Segarra (European Regional Science Association (ERSA), 2001)
In the international economic context, some changes affecting directly the behaviour of industries are taking place. These world level changes are due, in part, to the so called globalization process, that has modified the production activity, growing up the rivalry between firms. If we want to respond with success to the new situation a clear consecuence must generate, and that is the need to maintain a higher level of competitiveness in an industrial area. It is proven that there are competitive industries with a high employment level, a high productivity rate, and an important amount of exports. These industries are the basis of the regional economy, even tha national and, therefore, it is necesary to know the industry structure, and the reasons why a competitive advantage can be stablished. In our opinion, this is the way to get a wide vision of the dynamics of the system. In other words, we need to know which aspects, endogenous or exogenous, can give a competitive advantage to the industry. Spain in general, and in the Valencian Comunity, in particular, has an export-trade orientated structure: The tile industry, the shoe industry or the furniture one, are good examples of competitive industries, which are considered strategic parts of the valencian economic dynamics, even though they are also considered “traditional industries”. We have choosen the furniture industry to analize its competitiveness. The hypothesis that we want to contrast is that “in the Valencian Comunity, or more precisely, in the area of Valencia, an hightly competitive industrial cluster has been formed (defined as critical masses of unususal competitive success in particular fields by Porter, 1998). The relationships between its memebers, the competition and cooperation established among them, and the innovation generated inside it, implicate a dynamic behavior of the firms of the cluster and the competitiveness of the whole industry. In this study, we demonstrate the validity of the “cluster model” to explain competitiveness of the Valencian furniture industry, and how the factors that are implied are local.
Keywords: 330